Análisis del nivel de ventas de la Empresa UTEXT S.A. del cantón Montalvo - Flores Rivera, Víctor Hugo (2021)
This case study is developed in a descriptive way with a qualitative and quantitative approach, since the interview technique was used, these were carried out through a questionnaire addressed to the owner of the commercial premises "UTEXT", whose activity is buying and selling of textile products such as sheets, awnings, bedspreads, quilts etc. In the Canton Montalvo of the Province of Los Ríos. The objective of the study was to discover the sales levels and through said study to know the factors that influence the low performance of sales during 2018, 2019, 2020 and the first months of 2021. Based on the results obtained, evidence of sales growth; and then reflect a progressive decline during 2020. All this occurs due to different phenomena, the main one being the pandemic, the scarce publicity due to the slow adaptability to the changing environment, the bad appearance of the commercial premises, the presence of unfair competition. This research is subject to the parameters of the Commerce Degree of the Faculty of Administration, Finance and Informatics and is framed within the research line: Financial, administrative, tax, audit, control management. And since it is a private microenterprise, the research sub-line is involved: Public and private companies and institutions.